2004
DOI: 10.1002/bem.10181
|View full text |Cite
|
Sign up to set email alerts
|

An extremely low frequency magnetic field attenuates insulin secretion from the insulinoma cell line, RIN‐m

Abstract: In this study, we investigated the effects of exposure to an extremely low frequency magnetic field (ELFMF) on hormone secretion from an islet derived insulinoma cell line, RIN-m. We stimulated RIN-m cells to secrete insulin under exposure to an ELFMF, using our established system for the exposure of cultured cells to an ELFMF at 5 mT and 60 Hz, or under sham exposure conditions for 1 h and observed the effects. In the presence of a depolarizing concentration of potassium (45 mM KCl), exposure to ELFMF signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
0
23
1
Order By: Relevance
“…Media then were removed and replaced again with 25 mM glucose. The cells were incubated for 16 h, and the insulin content was determined by ELISA (18).…”
Section: Construction Of Short Interfering Rnas (Sirnas) and Transfecmentioning
confidence: 99%
“…Media then were removed and replaced again with 25 mM glucose. The cells were incubated for 16 h, and the insulin content was determined by ELISA (18).…”
Section: Construction Of Short Interfering Rnas (Sirnas) and Transfecmentioning
confidence: 99%
“…Most recently, we demonstrated that exposure to ELFMF for 1 or 2 h decreased insulin secretion in vitro [Sakurai et al, 2004[Sakurai et al, , 2005a. In normal rats, long-term exposure to ELFMF has been shown to lead to an increase in plasma insulin concentration [Laitl-Kobierska et al, 2002].…”
Section: Introductionmentioning
confidence: 98%
“…There are many evidences supporting the hypoglycemic ability of magnetic field exposure, but the optimum frequency and exposure time remain unclear (17)(18)(19)(20)(21). Öcal et al (10) investigated the effect of 5mT and 8mT on healthy and diabetic rats for the duration of 165 minutes for three weeks.…”
Section: Discussionmentioning
confidence: 99%